BEYOND SIGNAL AND NOISE: ACADEMICS GOES HOAX AND HOAXTIVISM - Leonard Chrysostomos Epafras; Fransiskus Agustinus Djalong; Hendrikus Paulus Kaunang (Universitas Gadjah Mada, 2018)
This article is a research report on the perception of hoax among the Indonesian academic community. Hoax is ancient, but in the present digital age, it sneaks into the center stage. Reflecting upon the global trends and shifting of international political landscape, it appears that hoax and its troops, e.g. “false news,” “alternative facts,” “disinformation,” etc. – immersed into the political language and practice. It may corroborate with the condition of “post-truth society” lamented by some scholars, in particular when it echoed in the present Indonesian political and religious landscape. The research focuses on hoax in general, and to introduce a term “hoaxtivism” in framing specific practice revolved in producing and consuming “hoax” as a signifier. We gauge the conversation on hoax within academic community, and locate it in the larger social process. The objective is to understand hoax and hoaxtivism beyond the moralistic evaluation and alarmist position, as overwhelmingly displayed in the public discussion.